2020
DOI: 10.22271/chemi.2020.v8.i3o.9349
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical constituents and overall acceptability of guava-papaya chutney during storage

Abstract: Chutney prepared from guava-papaya blends was analyzed for changes in chemical constituents and overall acceptability at monthly interval for three months storage period. Total sugars, reducing sugars and browning increased, while ascorbic acid, total carotenoids and total phenols decreased significantly in chutney during storage. Chutney prepared with 40 guava:60 papaya pulp ratio was most acceptable. The overall acceptability of chutney decreased significantly during three months storage period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Similar findings were reported by Sucheta et al (2017) during storage in guava-mango cheese storage for 90 days where browning increased from 0.25 to 0.37 during storage of 90 days. Kumar et al (2019b) found similar increase in browning of aonla-papaya cheese with storage. Singh et al (2020) reported similar increase of browning in fortified banana-guava cheese.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Similar findings were reported by Sucheta et al (2017) during storage in guava-mango cheese storage for 90 days where browning increased from 0.25 to 0.37 during storage of 90 days. Kumar et al (2019b) found similar increase in browning of aonla-papaya cheese with storage. Singh et al (2020) reported similar increase of browning in fortified banana-guava cheese.…”
Section: Resultssupporting
confidence: 52%
“…In an another study Kumar et al (2019b) studied storability of aonla-papaya cheese and observed gradual increase in total sugars (55.96-61.55%) whereas ascorbic acid (19-93%), total carotenoids (011-1.77%), total phenols (77-94%) and overall acceptability (7.7-8.1) decreased significantly in aonla-papaya cheese during storage of three months but an effective and reliable process has not been developed. However, fewer efforts have been made for utilizing these less exploited fruit crops, i.e., jamun and bael for developing value added products.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%
“…Organoleptic test is also referred as sensory analysis. In this test the qualities of the food ingredients and spices are determined by the sensory properties such as taste, smell, color and touch [20,23] . Organoleptic properties of jam are influenced by several parameters such as taste, flavor, appearance and texture.…”
Section: Organoleptic Attributes Of Jammentioning
confidence: 99%
“…Jam is the most preferred means of preserving papaya [19] . Like several other preserved product, papaya jam also undergo changes during storage [19,20] . There are very few reports showing influence of storage temperature on physiochemical and sensory parameters of papaya jam [19,20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation